Zika virus infection in Brazil and human rights obligations. Issue 1 (3rd November 2016) - Diniz, Debora; Gumieri, Sinara; Bevilacqua, Beatriz Galli; Cook, Rebecca J.; Dickens, Bernard M.
Abstract: The February 2016 WHO declaration that congenital Zika virus syndrome constitutes a Public Health Emergency of International Concern reacted to the outbreak of the syndrome in Brazil. Public health emergencies can justify a spectrum of human rights responses, but in Brazil, the emergency exposed prevailing inequities in the national healthcare system. The government's urging to contain the syndrome, which is associated with microcephaly among newborns, is confounded by lack of reproductive health services. Women with low incomes in particular have little access to such health services. The emergency also illuminates the harm of restrictive abortion legislation, and the potential violation of human rights regarding women's health and under the UN Conventions on the Rights of the Child and on the Rights of Persons with Disabilities. Suggestions have been proposed by which the government can remedy the widespread healthcare inequities among the national population that are instructive for other countries where congenital Zika virus syndrome is prevalent. Abstract : The Brazilian outbreak of congenital Zika virus syndrome triggers proposals to remedy prevailing health service inequities for women, children with special needs, and disabled people.